Tuning the 1T′/2H phases in WxMo1−xSe2 nanosheets. Issue 6 (18th January 2023) - Sokolikova, Maria S.; Cheng, Gang; Och, Mauro; Palczynski, Pawel; El Hajraoui, Khalil; Ramasse, Quentin M.; Mattevi, Cecilia
Abstract : Nanomaterial morphology, chemical composition and 1T′/2H crystal phase tuning is achieved in colloidal W x Mo1− x Se2  nanosheets synthesised by a direct colloidal reaction. Abstract : Controlling materials' morphology, crystal phase and chemical composition at the atomic scale has become central in materials research. Wet chemistry approaches have great potential in directing the material crystallisation process to achieve tuneable chemical compositions as well as to target specific crystal phases. Herein, we report the compositional and crystal phase tuneability achieved in the quasi-binary W x Mo1− x Se2 system with chemical and crystal phase mixing down to the atomic level. A series of W x Mo1− x Se2 solid solutions in the form of nanoflowers with atomically thin petals were obtained via a direct colloidal reaction by systematically varying the ratios of transition metal precursors. We investigate the effect of selenium precursor on the morphology of the W x Mo1− x Se2 material and show how using elemental selenium can enable the formation of larger and distinct nanoflowers. While the synthesised materials are compositionally homogeneous, they exhibit crystal phase heterogeneity with the co-existing domains of the 1T′ and 2H crystal phases, and with evidence of MoSe2 in the metastable 1T′ phase. We show at single atom level of resolution, that tungsten and molybdenum can be found in both the 1T′ and 2H lattices. The formation of heterophase 1T′/2H W x Mo1− x Se2 electrocatalysts allowed for a considerable improvement in the activity for the acidic hydrogen evolution reaction (HER) compared to pristine, 1T′-dominated, WSe2 . This work can pave the way towards engineered functional nanomaterials where properties, such as electronic and catalytic, have to be controlled at the atomic scale.